EU extension to the East and exporting jobs: Tax harmonization may hurt more and benefit less - Ognian N. Hishow (Stiftung Wissenschaft und Politik (SWP), 2004)
The recent accession of eight East European economies to the EU gave the everlasting discussion in Germany about job exports to low cost countries a new boost. What critics overlook is that since 1990 two regions have been integrating that strongly differ in their capital endowments and productivity levels. The result is, among other things, a slight reorientation of German capital exports towards the new entrants. This should be accepted, not prevented by means of tax harmonization, which would reduce the rate of growth in the new member states. This would simply increase the cost to the West, in the form of higher transfers. (SWP Comments / SWP)
Keywords: 320